Transcriptome Analysis of Maize Immature Embryos Reveals the Roles of Cysteine in Improving Agrobacterium Infection Efficiency - Liu, Yan; Zhang, Zhiqiang; Fu, Junjie; Wang, Guoying; Wang, Jianhua; Liu, Yunjun (Frontiers in Plant Science, 2017)
Maize Agrobacterium-mediated transformation efficiency has been greatly improved in recent years. Antioxidants, such as cysteine, can significantly improve maize transformation frequency through improving the Agrobacterium infection efficiency. However, the mechanism underlying the transformation improvement after cysteine exposure has not been elucidated. In this study, we showed that the addition of cysteine to the cocultivation medium significantly increase the Agrobacterium infection efficiency of hybrid HiII and inbred line Z31 maize embryos. Reactive oxygen species contents were higher in embryos treated with cysteine than that without cysteine, due to the high efficient Agrobacterium infection. We further investigated the mechanism behind cysteine-related infection efficiency increase using transcriptome analysis. The results showed that the cysteine treatment up-regulated 939 genes and down-regulated 549 genes in both Z31 and HiII. Additionally, more differentially expressed genes were found in HiII embryos than those in Z31 embryos, suggesting that HiII was more sensitive to the cysteine treatment than Z31. GO analysis showed that the up-regulated genes were mainly involved in the oxidation reduction process. The up-regulation of these genes could help maize embryos to cope with the oxidative stress stimulated by Agrobacterium infection. The down-regulated genes were mainly involved in the cell wall and membrane metabolism, such as aquaporin and expansin genes. Decreased expression of these cell wall integrity genes could loosen the cell wall, thereby improving the entry of Agrobacterium into plant cells. This study offers insight into the role of cysteine in improving Agrobacterium-mediated transformation of maize immature embryos.